AB0833-HPR Health-related physical fitness testing in physiotherapy practice – reliability and feasibility. (23rd January 2014) - Tveter, A. T.; Moseng, T.; Dagfinrud, H.; Holm, I.
Abstract : Background: People with musculoskeletal conditions (MSCs) tend to be less physically active 1 and more deconditioned than healthy controls 2 ;3 . Thus, physiotherapists seeing patients with MSCs should include an individually tailored exercise program in the treatment plan. According to current recommendations, these exercise programs should focus on health-related physical fitness 4 . For measuring patients' physical fitness, reliable and feasible instruments are needed. Objectives: To examine reliability and feasibility of frequently used patient-reported and performance-based instruments for measuring health-related physical fitness in patients with a variety of MSCs. Methods: In a test-retest study, 81 patients were tested twice one week apart. Patients conducted five performance-based tests (the 6 min walk test (6MWT), the stair test (ST), the handgrip test, the 30 sec sit-to-stand test (30sSTS) and the modified fingertip-to-floor test (FTF)) and answered two questionnaires (the Self-assessed physical fitness questionnaire and the COOP/WONCA Charts). Reliability and measurement error was calculated with ICC2.1 or weighted kappa and Standard Error of Measurement (SEM) and Smallest Detectable Change (SDC). ICC2.1 and weighted kappa values of <0.70 were considered acceptable. Results: All performance-based tests and the Self-assessed physical fitness questionnaire and three of six charts in the COOP/WONCA Charts showed acceptable reliability. SDC90% was calculated to 49 meters, 8 sec and 4 kg for the 6MWT, the ST and the handgrip test, respectively. Correspondingly, 4 sit-to-stands and 9 cm fingertip-to-floor distance was shown for the 30sSTS and the FTF test. Changes of two points were needed to detect changes beyond measurement error in the Self-assessed physical fitness questionnaire. The 6MWT was the most time consuming, with all other instruments each taking less than 3 min to complete. About 40% needed assistance in answering the COOP/WONCA Charts, while the corresponding value for the Physical Fitness Quetionnaire was about 20%. Conclusions: All instruments seem feasible for use in patients with MSCs. The 6MWT, the ST, the handgrip test and the Self-assessed physical fitness questionnaire can be recommended as reliable instruments with acceptable measurement error, while the 30sSTS test and the modified FTF test showed high variability for use in assessing change in health-related physical fitness. The COOP/WONCA Chart might be more suitable for screening purposes. References: Farr et al. Physical activity levels in patients with early knee osteoarthritis measured by accelerometry. Arthritis Rheum 2008; 59(9):1229-1236. Ryan et al. Individuals with chronic low back pain have a lower level, and an altered pattern, of physical activity compared with matched controls: an observational study. Aust J Physiother 2009; 55(1):53-58. Hodselmans et al. Nonspecific chronic low back pain patients are deconditioned and have an increased body fat percentage. Int J Rehabil Res 2010; 33(3):268-270. Nelson et al. Physical activity and public health in older adults: recommendation from the American College of Sports Medicine and the American Heart Association. Med Sci Sports Exerc 2007; 39(8):1435-1445. Disclosure of Interest: None Declared